Effectiveness of the local infiltration of anti-snake venom on experimental mice envenomed with Russell's viper (Vipera russelii ) venom - Aung, Wing; Khin, Maung Maung (Department of Medical Research (Lower Myanmar), Ministry of Health, Myanmar, 2012)
The immediate administration of intravenous (IV) anti-snake venom (ASV) is an ideal, safe and effective treatment, and intramuscular (IM) ASV administration also has a value as a first aid measure for Russell's viper bite patients. In this study, the effectiveness of different dosages of ASV infiltrated locally at the site of Russell's viper venom (RVV) injection on experimental mice was studied at various time intervals after envenomation, and then compared with those administered intramuscularly and intravenously. The minimum effective doses (EDs100) of ASV given locally, intramuscularly and intravenously on envenomed mice were found to be 50, 100 and 25 times w/w greater than that of minimal lethal dose (MLD) of RVV, respectively. The obvious neutralizing effect of ASV infiltrated locally was observed if given within an hour after envenomation. It could be suggested that local infiltration of ASV may be an effective first aid measure superior to intramuscular administration in the management of Russell's viper bite envenomation.